Pengaruh Faktor Makroekonomi Terhadap Resiko Pembiayaan Bank Syariah: Studi Pada Bank Umum Syariah di Indonesia Tahun 2015-2018 - Rizki Fitriansyah (Islamic Economics Journal, 2019)
Sharia banks are one of the financial institutions that are currently still developing in Indonesia. Like other financial institutions, Sharia banks also have a risk faced, namely the risk of financing. The risk of financing in Sharia banks is commonly known as the risk of financing problems. The level of problem financing in Islamic banks is one indicator of the level of the soundness of banks. The size of the problematic financing level is partly due to bad financing due to the sluggishness of the real sector in response to macroeconomic conditions. Financial system instability (financial crisis) in addition to influencing banking liquidity also encouraged an increase in problem financing. From a macroeconomic perspective, Indonesia’s current economic conditions of public concern include the exchange rate and the inflation rate.This research was conducted to determine the effect of macroeconomic factors, exchange, and comparison, on interest rates, Sharia Commercial Banks in Indonesia. The data used in this study are secondary data obtained from Sharia Banking Statistics issued by the Financial Services Authority (OJK) and data from Bank Indonesia (BI). Analysis of the technique in this study uses multiple linear regression analysis techniques. The results showed that the rupiah exchange rate and the exchange rate were significant for troubled funds at Sharia Commercial Banks. Meanwhile, the exchange rate is significant towards problem financing at Sharia Commercial Banks, while the exchange rate is significant against problem financing at Sharia Commercial Banks.